2010
DOI: 10.4055/cios.2010.2.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcomes of Triplane and Tillaux Fractures of the Ankle in Adolescence

Abstract: BackgroundTo identify the fracture configuration and treatment results for patients with triplane and Tillaux fractures in the ankle joint.MethodsA retrospective study was performed on 14 patients with a more than one year follow-up. This study investigated the fracture configuration, concomitant fibula fracture, treatment methods and complications. The treatment outcomes were analyzed using modified Weber protocol.ResultsAmong the 14 cases, 11 were triplane fractures and 3 were Tillaux fractures. Seven were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 12 publications
1
24
0
Order By: Relevance
“…The mean follow-up period was 14.2 (range, [9][10][11][12][13][14][15][16][17][18][19][20] weeks. All patients had excellent outcome.…”
Section: Resultsmentioning
confidence: 99%
“…The mean follow-up period was 14.2 (range, [9][10][11][12][13][14][15][16][17][18][19][20] weeks. All patients had excellent outcome.…”
Section: Resultsmentioning
confidence: 99%
“…Although CT scans and radiographs were found to be accurate to within 1 mm 50% of the time, the authors found that CT scans are more sensitive in detecting fracture displacements larger than 2 mm. 21 In addition, Kim et al 22 found that a better understanding of fracture configuration, such as that provided by CT, correlated with improved outcomes with triplane and Tillaux fractures. The role of magnetic resonance imaging (MRI) remains unclear.…”
Section: C 2dmentioning
confidence: 97%
“…For medial triplane fractures, open reduction using an anteromedial approach has been proposed, whereas for the lateral triplane fractures an anterolateral approach is employed [13].…”
mentioning
confidence: 99%
“…Surgical interventions for the precise and safe reduction of displaced fractures include percutaneous Kirschner wire fixation or open reduction and internal fixation with cannulated cancellous transepiphyseal screws with special precautions to eschew the penetration of both the articular surface and physis [7,13,14]. For medial triplane fractures, open reduction using an anteromedial approach has been proposed, whereas for the lateral triplane fractures an anterolateral approach is employed [13].…”
mentioning
confidence: 99%
See 1 more Smart Citation